REASONS FOR COMMITTING OR AVOIDING ACADEMIC DISHONESTY AND SOLUTIONS AMONG PRECLINICAL DENTAL STUDENTS DURING THE COVID-19 PANDEMIC: A GROUNDED THEORY APPROACH - Asmara, Aditya Hari; Rahayu, Gandes Retno; Prihatiningsih, Titi Savitri (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Virtual education implemented during the COVID-19 pandemic has various limitations and one of the biggest challenges is academic dishonesty. Global research related to reasons for committing or avoiding academic dishonesty among preclinical dental students during the COVID-19 pandemic is still very limited. This study aimed to explain the reasons for committing and avoiding academic dishonesty as well as the solutions among preclinical dental students during the COVID-19 pandemic.Methods: The grounded theory approach was used by conducting semi-structured virtual in-depth interviews with preclinical dental students. Participants were selected using purposive, snowball, and maximum variation sampling. Interview transcripts were analyzed using a constant comparative approach.Results: The reasons for committing and avoiding academic dishonesty as well as the solutions among preclinical dental students during the COVID-19 pandemic can be explained by the same two factors: internal and external. Internal factors are students, while external factors are teachers and learning activities.Conclusion: Teaching adequate professionalism to students, effective faculty development, and "especially" improving learning activities can be preventive efforts against academic dishonesty.